Mechanisms underlying enhanced Cd translocation and tolerance in roots of Populus euramericana in response to nitrogen fertilization. (October 2019) - Song, Junyu; Finnegan, Patrick M.; Liu, Wenhui; Li, Xiang; Yong, Jean W.H.; Xu, Jiuting; Zhang, Qi; Wen, Yuxin; Qin, Kexin; Guo, Jinze; Li, Ting; Zhao, Chang; et al.
Graphical abstract: Highlights: Cd absorption and accumulation in roots increased under N-deficient condition. Fine root length was tightly correlated with Cd absorption and Cd accumulation in roots. Cd uploading in roots and Cd translocation to shoots were decrased by N deficiency. Genes for Cd detoxification, uploading and antioxidant defense in roots were up-regulated by N application. N-stimulated Cd detoxification, uploading and antioxidation in roots contributed to Cd translocation. Abstract: A pot experiment was conducted to evaluate how nitrogen (N) availability influences cadmium (Cd) absorption, translocation and stress tolerance in roots of Populus euramericana . Seedling growth was sensitive to N deficiency, but it was unaltered by Cd exposure. Cadmium absorption by roots was promoted by N deficiency, resulting in a higher root Cd concentration compared to the N-sufficient condition. Fine-root length was tightly correlated (R 2 = 0.73) with Cd concentration in roots, indicating that vigorous fine-root proliferation under N deficiency contributed to active absorption and accumulation of Cd in roots. Despite accumulation in roots, Cd translocation from roots to shoots was less active under N deficiency compared to N sufficiency. This was related to elevated glutathione reductase (GR) activity and glutathione (GSH) levels in roots after N application, which may not only promote antioxidant defence, but also facilitate the formation of GSH–Cd complexes that are uploaded into root cylinders. Nitrogen application also promoted antioxidant defense in roots via increased production of phytohormones and the level of enzymatic and non-enzymatic antioxidants. Transcript levels for genes responsible for antioxidant defense, Cd detoxification and Cd uploading were increased in roots by N application. The N-stimulated Cd tolerance, detoxification and uploading in roots are factors likely to promote Cd translocation from roots to shoots, which may enhance the biological capacity of this poplar species for phytoremediation of Cd pollution.